The Part-Time-Society's Activity and Mobility Patterns - Jan S. Kowalski; Axel J. Schaffer (European Regional Science Association (ERSA), 2005)
In his article 'What about People in Regional Science?' Hägerstrand (1970) identifies time and space constraints as dominating determinants of each individual's activity pattern. The paper at hand follows this idea, but considers the whole society's accumulated time budget instead. Based on a Socio-Economic Input-Output Table (SIOT) in time and monetary) units, activity patterns of three age groups (<18 years; 18-65 years; >65 years) are analyzed in further detail. Since the applied concept allows for a simultaneous analysis of time use and time receipts, inter-generational linkages can be identified as well. Care activities, for example, often require time inputs from the middle age group (18-65 years). However, the beneficiaries belong in the majority to the young and the old age group. Obviously, the age groups' activity patterns come along with specific mobility needs. Therefore, the second aim of the study is to identify mobility patterns – at an aggregated level – as well. Finally, the paper gives a first insight into potential changes of activity patterns and mobility patterns in particular, that could be initiated by the realization of a part-time-society. The latter is characterized by a strong reduction of individual (paid) working time, flexible time schedules and a strengthening of social activities.
Keywords: 330